Hubungan Dukungan Keluarga dengan Keberhasilan ASI Eksklusif - Rizki Muji Lestari; Sri Mularsih (Akademi Keperawatan Yarsi Samarinda, 2026)
Family support is the external factor that has the greatest influence on the success of exclusive breastfeeding. The existence of family support, especially from the husband, will have an impact on increasing the confidence or motivation of mothers in breastfeeding. The purpose of this study was to determine the relationship between family support and the success of exclusive breastfeeding in the Campurdarat Community Health Center work area. The design of this study was a quantitative correlational study with a cross-sectional approach. The sampling technique used was purposive sampling with a sample size of 38 respondents. From the results of data analysis using Chi Square, it was found that there was a relationship between family support and the success of exclusive breastfeeding (0.000). This study shows that family support is good. This can occur because it is influenced by several factors such as education level and employment status.